2018
DOI: 10.1063/1.5033914
|View full text |Cite
|
Sign up to set email alerts
|

Improved excitation mode selectivity of high-Tc superconducting terahertz emitters

Abstract: Articles you may be interested in Circularly polarized terahertz radiation monolithically generated by cylindrical mesas of intrinsic Josephson junctions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…We have already studied the radiation characteristics of various types of SAMs by using the square shape rigs shown in Figure 2 a [ 43 , 52 ] and the cylindrical shape rigs displayed in Figure 2 b [ 65 ] and confirmed that almost similar electric and cooling properties can be obtained. These rigs enable us to make easy electrical contact to the SAMs as well as to obtain high heat exhausting characteristics from the SAMs.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…We have already studied the radiation characteristics of various types of SAMs by using the square shape rigs shown in Figure 2 a [ 43 , 52 ] and the cylindrical shape rigs displayed in Figure 2 b [ 65 ] and confirmed that almost similar electric and cooling properties can be obtained. These rigs enable us to make easy electrical contact to the SAMs as well as to obtain high heat exhausting characteristics from the SAMs.…”
Section: Methodsmentioning
confidence: 80%
“…The SAMs were sandwiched by two metallic film coated sapphire substrates in order to make good electrical and thermal contacts. These rigs were fixed by four screws, then, a hemispherical-shaped Si lens with a diameter of 4 mm was attached to the top of the front sapphire substrate [ 43 , 52 , 65 ]. The electromagnetic waves from the SAMs were collected by the lens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Layered high-temperature superconductor Bi 2 Sr 2 CaCu 2 O 8+ (Bi-2212) may provide an alternative technology for creation of cryogenic THz sources [9][10][11][12][13][14][15][16][17][18][19][20][21]. Bi-2212 represents a natural stack of atomic scale intrinsic Josephson junctions (IJJ's) [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%